Indicadores de CT&I dos INCTs de São Carlos-SP na dinâmica da produção da ciência - Guimarães, Vera Aparecida Lui (Universidade Federal de São Carlos, 2016)
The theme of this research is the conformation of the new production of science, especially that realized in the ambit of the seven National Institutes of Science and Technology of São Carlos (city of the interior of the state of São Paulo, Brazil). From the theoretical point of view, this study is part of the field of Social Studies of Science and Technology, seeking in the Sociology of Science theoretical elements that allow us to understand the complexities of the new modes of producing scientific knowledge. The research was guided by the following question: do the science, technology and innovation indicators of the São Carlos’ INCTs point to changes in the form of production of science after its implementation? The hypotheses were that the São Carlos’ INCTs provided: a) the strengthening of university interaction with the productive sector and the transfer of knowledge produced; and b) the impact on society in terms of scientific education and dissemination of science. The general objective was to identify and evaluate ST&I indicators of the São Carlos’ INCTs, which allowed examining the dynamics of knowledge production and the scientific, educational and social impacts achieved since the implementation of this Program in São Carlos. The following specific objectives were also established: 1) to seek in the theoretical framework of Sociology of Science elements that allow to understand the organization of the scientific community, the forms of production of knowledge and the policies of science, technology and innovation; 2) to describe the profile of the INCTs, placing them in the main teaching and research institutions of São Carlos-SP; 3) analyze the dynamics of the INCTs from five dimensions: advancement of knowledge; Networking; Transfer of knowledge to society; Advancement of competence and internationalization; 4) to analyze the scientific and technological production and networks of scientific collaboration of the principal investigators of the INCTs; 5) identify the practice, results and impact of education and scientific dissemination within the scope of the INCTs; and 6) present the coordinators’ perception of this new configuration and organization of science and its impacts on society. The research is an exploratory and descriptive case study developed based on quantitative and qualitative approaches, through bibliometric and scientometric analyzes, social networks analysis, and the analysis of the perceptions of the coordinators obtained with the questionnaire. The methodological procedures involved data collection from different sources (Curriculum Lattes, Project Monitoring Reports and other documents) and questionnaire application to the INCT coordinators. Among the main results obtained are the high index of international bibliographic production published by the INCT in the period between 2009 and 2013, with emphasis on scientific articles and works in events; the training of human resources and the involvement with activities of education and scientific dissemination, particularly in the INCTs of USP. The evaluation of the INCTs in the view of the coordinators was that these programs produced important results in terms of advancement of knowledge, training of human resources, transfer of knowledge to society, internationalization, diffusion and scientific education, contributing to society in the solution of health problems, security and energy, the environment and learning and education.
Keywords: National Institutes of Science and Technology; Indicators; Sociology of Science; Scientific Community; Institutos Nacionais de Ciência e Tecnologia; Sociologia da ciência; Indicadores; Comunidade científica; Política científica, tecnológica e de inovação; CIENCIAS HUMANAS